2020
DOI: 10.1007/jhep01(2020)111
|View full text |Cite
|
Sign up to set email alerts
|

The holographic landscape of symmetric product orbifolds

Abstract: We investigate the growth of coefficients in the elliptic genus of symmetric product orbifolds at large central charge. We find that this landscape decomposes into two regions. In one region, the growth of the low energy states is Hagedorn, which indicates a stringy dual. In the other, the growth is much slower, and compatible with the spectrum of a supergravity theory on AdS 3 . We provide a simple diagnostic which places any symmetric product orbifold in either region. We construct a class of elliptic genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
(82 reference statements)
0
21
0
Order By: Relevance
“…with t/b ∈ have a basis of unwrapped elliptic genera of N = (2, 2) CFTs. We note that since [23] showed that if b > t, the symmetric product cannot grow slowly, for such cases U t,b = 0. This means that the CFTs in the stronger conjecture have to have c ≤ 6.…”
Section: The Landscape Of Symmetric Orbifold Theories 41 a Conjecturmentioning
confidence: 83%
See 4 more Smart Citations
“…with t/b ∈ have a basis of unwrapped elliptic genera of N = (2, 2) CFTs. We note that since [23] showed that if b > t, the symmetric product cannot grow slowly, for such cases U t,b = 0. This means that the CFTs in the stronger conjecture have to have c ≤ 6.…”
Section: The Landscape Of Symmetric Orbifold Theories 41 a Conjecturmentioning
confidence: 83%
“…This implies that for a fixed t, there is only a relatively small number of such terms, roughly ∼ t 2 /12. The analysis of (2.12) in [23] also established that b 2 > t implies Hagedorn growth. This implies that if ϕ is the elliptic genus of a bona fide CFT, i.e.…”
Section: Spectrum Of the Symmetric Orbifoldmentioning
confidence: 92%
See 3 more Smart Citations